2022
DOI: 10.3389/fpsyg.2022.841189
|View full text |Cite
|
Sign up to set email alerts
|

The Role of General Attitudes and Perceptions Towards Vaccination on the Newly-Developed Vaccine: Results From a Survey on COVID-19 Vaccine Acceptance in China

Abstract: BackgroundVaccination has been considered one of the most effective public health interventions. In the context of the global epidemic of coronavirus disease 2019 (COVID-19), it remains unclear what role general vaccination attitudes and perceptions have on the acceptance of COVID-19 vaccine.ObjectiveThis study aims to explore the impact of general attitudes and perceptions toward vaccination on the acceptance of a newly developed vaccine, taking COVID-19 vaccines as an example.MethodA cross-sectional survey w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 57 publications
1
5
0
Order By: Relevance
“…The perceptions of the HCPs were linked to their attitudes towards the COVID-19 vaccinations. In consonance with our findings are the findings of Jing et al [ 25 ] in China, Adane et al [ 9 ] in Ethiopia, and Amponsah-Tabi et al [ 14 ] in Ghana. Positive perceptions of the COVID-19 vaccination among the HCPs imply a good impression of the role of the COVID-19 vaccine.…”
Section: Discussionsupporting
confidence: 93%
“…The perceptions of the HCPs were linked to their attitudes towards the COVID-19 vaccinations. In consonance with our findings are the findings of Jing et al [ 25 ] in China, Adane et al [ 9 ] in Ethiopia, and Amponsah-Tabi et al [ 14 ] in Ghana. Positive perceptions of the COVID-19 vaccination among the HCPs imply a good impression of the role of the COVID-19 vaccine.…”
Section: Discussionsupporting
confidence: 93%
“…It was found that 75% of the participants believed in the vaccine's efficacy. The studies conducted in Nepal (78.4%) and China (75.8%) reported similar or higher results [27,28]. Studies conducted in Pakistan and Ethiopia showed that people's perception of vaccine effectiveness was relatively low.…”
Section: Discussionmentioning
confidence: 78%
“…Our survey showed that about two-thirds of respondents had a positive attitude about vaccine protection against COVID-19 before vaccines were produced. A similar study was conducted in China at the end of 2020, one month before the COVID-19 vaccine became available [ 14 ]. In this study, approximately half of the respondents expressed no hesitancy toward vaccines, while 28% were hesitant, and 21% refused to be vaccinated if the vaccine would be developed and approved [ 14 ].…”
Section: Discussionmentioning
confidence: 99%
“…A similar study was conducted in China at the end of 2020, one month before the COVID-19 vaccine became available [ 14 ]. In this study, approximately half of the respondents expressed no hesitancy toward vaccines, while 28% were hesitant, and 21% refused to be vaccinated if the vaccine would be developed and approved [ 14 ]. Keeping in mind that China has its own vaccine production, our finding was encouraging at that moment.…”
Section: Discussionmentioning
confidence: 99%